Moderate and Timely Water Intake Followed By Micturition Reduces Frequency of Recurrent Urinary Tract Infections and the Prevalence of Virulent Uropathogens in Adult Women - El-Reshaid, Kamel; Al-Bader, Shaikha (International Journal of Innovative Research in Medical Science, 2020)
Urinary tract infection (UTI) is the most common type of infection in women. Preventive measures included local hygiene, clothing, diet, limiting activities, and prophylactic antibiotics. In this study; we evaluated the role of a simple technique of 5-timely oral water flushing of the urinary bladder in its prevention. The technique entailed an intake of 250 ml of plain water followed by micturition 15-30 minute later at; early morning, 30 minute after the 3 daily meals and 1 hour before night sleep. Moreover, married women had an additional similar bolus intake 30 minute before sexual intercourse and micturition immediately after coitus. This prophylactic regimen has been evaluated in 422 adult non-menopausal females with high-rate of recurrent UTI (>2 UTI/year) for a median duration of 33 months. Married women; had higher rate of UTI/patient year and incidence of non-E coli bacteriuria compared to non-married ones. Our prophylactic technique resulted in; (a) decrease in UTI rate/patient year on follow up from 2.3(0.8) to 0(0.3), (b) clearance of bacteriuria in 69% of women, and decrease of non-E coli pathogens from 31% to 2% (p< 0.001). The latter was due to limiting the use of antibiotics. Married women had similar encouraging results. In conclusion; moderate and timely water intake followed by micturition reduces frequency of recurrent urinary tract infections and the prevalence of virulent uropathogens in adult women.